1996
DOI: 10.1016/s0009-9236(96)90133-2
|View full text |Cite
|
Sign up to set email alerts
|

Formation of morphine from codeine in Chinese subjects of different CYP2D6 genotypes*

Abstract: Codeine and morphine pharmacokinetics among different CYP2D6 genotypes was compared in this study. Polymerase chain reaction tests were used to determine CYP2D6 genotypes in leukocyte deoxyribonucleic acid in 32 unrelated volunteers. Based on the genotypes, subjects were categorized into three groups: homozygous C/C188 (n = 8), heterozygous C/T188 (n = 12), and homozygous T/T188 (n = 12). Each subject was given a single oral dose of 30 mg codeine phosphate tablet after overnight fasting. Plasma concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The PMs had very low or undetectable concentrations of morphine. The partial clearance of morphine formation also showed a significant decreasing trend among homozygous CYP2D6*10, heterozygous CYP2D6*10, and reference Chinese 169 …”
Section: Cyp2d6mentioning
confidence: 87%
“…The PMs had very low or undetectable concentrations of morphine. The partial clearance of morphine formation also showed a significant decreasing trend among homozygous CYP2D6*10, heterozygous CYP2D6*10, and reference Chinese 169 …”
Section: Cyp2d6mentioning
confidence: 87%
“…Similarly, Tseng et al. [16] reported that the partial metabolic clearance of codeine to morphine in homozygotes for CYP2D6 * 10 is more than four times lower than that for the wild‐type. The findings suggest that the polymorphism produced by CYP2D6 * 10 play a more important role than previously thought in the treatment of Japanese patients with drugs metabolized by CYP2D6.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, over the past three decades, pharmacogenetic research has found substantial differences among ethnic groups in the metabolism, clinical effectiveness and side-effect profiles of many drugs [45]; however, only a few studies have examined ethnic differences in the effects of pain medications. A pharmacokinetic study found ethnic differences (between non-Hispanic whites, African–Americans and Asian participants) in the effectiveness of codeine [46] and the metabolism of morphine may differ between non-Hispanic whites and Chinese patients [47]. Rabow and Dibble examined ethnic and country-of-origin differences in patients with terminal and end-stage chronic illness and found no differences in pain between Asian, African–American and Latino patients [48], although they reported significantly more pain than non-Hispanic whites.…”
Section: Disparities In Treatmentmentioning
confidence: 99%